Suriname : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper focuses on constructing a high-frequency economic growth indicator for Suriname. Most economic data for Suriname are available only with a substantial time lag and on a low-frequency basis, impeding such analyses. This paper presents a simple econometric model that closely approximates GDP in recent years. The model estimates are used to construct a monthly indicator of economic activity for Suriname. The indicator provides information about the pace of economic activity close to real time, typically with a one- to two-month lag.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet